Performance of Thailand's universal health coverage scheme: Evaluating the effectiveness of annual public hearings. (9th October 2020) - Kantamaturapoj, Kanang; Marshall, Aniqa I.; Chotchoungchatchai, Somtanuek; Kiewnin, Kamonwan; Patcharanarumol, Walaiporn; Tangcharoensathien, Viroj
Abstract: Background: Legislative provisions in Thailand's National Health Security Act 2002 mandate annual public hearings for providers, beneficiaries and other stakeholders in order to improve the performance of the Universal Health Coverage Scheme (UCS). Objective: This study aims to explore the annual public hearing process, evaluate its effectiveness and propose recommendations for improvement. Method: In‐depth interviews were conducted with 29 key informants from various stakeholder groups involved in annual public hearings. Results: The evaluation showed that the public hearings fully met the criteria of influence over policy decision and partially met the criteria of appropriate participation approach and social learning. However, there are rooms for improvement on public hearing's inclusiveness and representativeness of participants, adequacy of information and transparency. Conclusions: Three recommendations were proposed a) informing stakeholders in advance of the agenda and hearing process to enable their active participation; b) identifying experienced facilitators to navigate the discussions across stakeholders with different or conflicting interests, in order to reach consensus and prioritize recommendations; and c) communicating policy and management responses as a result of public hearings to all stakeholders in a timely manner.